Exploring The Role of Teachers in the Implementing English Language Teaching Strategies at SMPN 2 Telaga - Vira Zamrudah Ikram Salsabila; Novriyanto Napu; Sri Widyarti Ali (Transbahasa, 2026)
This study aims to explore the roles of teachers in implementing English language teaching strategies at SMPN 2 Telaga. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis of lesson plans. The findings reveal two contrasting pedagogical orientations. One teacher adopts a teacher-centered approach that emphasizes structured instruction and linguistic accuracy but limits student interaction. In contrast, the other teacher applies a student-centered and communicative approach that actively promotes student engagement, participation, and confidence in using English. The study further indicates that the student-centered approach is more effective in fostering meaningful learning, although challenges remain in addressing differences in students’ confidence and participation levels. These findings highlight that effective English language teaching requires the integration of pedagogical, communicative, and affective aspects. Teachers are therefore encouraged to balance structured instruction with interactive learning, provide both corrective and supportive feedback, and create a motivating classroom environment to enhance student engagement and learning outcomes.